The nuclear factor-erythroid 2-related factor/heme oxygenase-1 axis is critical for the inflammatory features of type 2 diabetes–associated osteoarthritis - Vaamonde-Garcia, Carlos (J Biol Chem, 2017)
Epidemiological findings support the hypothesis that type 2 diabetes mellitus (T2DM) is a risk factor for osteoarthritis (OA). Moreover, OA cartilage from patients with T2DM exhibits a greater response to inflammatory stress, but the molecular mechanism is unclear. To investigate whether the antioxidant defense system participates in this response, we examined here the expression of nuclear factor-erythroid 2-related factor (Nrf-2), a master antioxidant transcription factor, and of heme oxygenase-1 (HO-1), one of its main target genes, in OA cartilage from T2DM and non-T2DM patients as well as in murine chondrocytes exposed to high glucose (HG). Ex vivo experiments indicated that Nrf-2 and HO-1 expression is reduced in T2DM versus non-T2DM OA cartilage (0.57-fold Nrf-2 and 0.34-fold HO-1), and prostaglandin E(2) (PGE(2)) release was increased in samples with low HO-1 expression. HG-exposed, IL-1β-stimulated chondrocytes had lower Nrf-2 levels in vitro, particularly in the nuclear fraction, than chondrocytes exposed to normal glucose (NG). Accordingly, HO-1 levels were also decreased (0.49-fold) in these cells. The HO-1 inducer cobalt protoporphyrin IX more efficiently attenuated PGE(2) and IL-6 release in HG+IL-1β-treated cells than in NG+IL-1β-treated cells. Greater reductions in HO-1 expression and increase in PGE(2)/IL-6 production were observed in HG+IL-1β-stimulated chondrocytes from Nrf-2(−/−) mice than in chondrocytes from wild-type mice. We conclude that the Nrf-2/HO-1 axis is a critical pathway in the hyperglucidic-mediated dysregulation of chondrocytes. Impairments in this antioxidant system may explain the greater inflammatory responsiveness of OA cartilage from T2DM patients and may inform treatments of such patients.